Low-temperature toughness of direct quenched offshore steel. (November 2015) - Cheng, T. C.; Yu, C.; Yang, T. C.; Huang, C. Y.; Lin, H. C.; Shiue, R. K.
Abstract : The ductile-to-brittle transition of direct quenched and tempered martensite begins at 243 K, and the impact energy of the superficial region of the steel plate decreases from 104 J (243 K) to 50 J (213 K). In contrast, the ductile-to-brittle transition of bainite begins at room temperature. The impact energies of the central region of the steel plate at different testing temperatures are 107 J at room temperature (300 K), 47 J at 253 K and 26 J at 213 K. The presence of bainite in the central region of the direct quenched steel plate significantly degrades the low-temperature toughness of offshore steel.